On automorphism groups of some modules - Dashkova, O.Yu. (Algebra and Discrete Mathematics, 2006)
In this paper we investigated ZG-module A, where G is either nilpotent or soluble group of infinite special rank. It is described the construction of these modules in the case, if for any proper subgroup H of infinite special rank of group G the quotient module A/CA(H) is a noetherian Z-module.